Aldehydes and ketones influence reactivity and selectivity in nickel-catalysed Suzuki–Miyaura reactions. Issue 7 (16th January 2020) - Cooper, Alasdair K.; Leonard, David K.; Bajo, Sonia; Burton, Paul M.; Nelson, David J.
Abstract : Aldehydes and ketones can have beneficial or detrimental effects on nickel-catalysed reactions. When present on the aryl halide, excellent site-selectivity can be achieved; when present as additives, they inhibit the reaction. Abstract : The energetically-favorable coordination of aldehydes and ketones – but not esters or amides – to Ni 0 during Suzuki–Miyaura reactions can lead either to exquisite selectivity and enhanced reactivity, or to inhibition of the reaction. Aryl halides where the C–X bond is connected to the same π-system as an aldehyde or ketone undergo unexpectedly rapid oxidative addition to [Ni(COD)(dppf)] (1 ), and are selectively cross-coupled during competition reactions. When aldehydes and ketones are present in the form of exogenous additives, the cross-coupling reaction is inhibited to an extent that depends on the strength of the coordination of the pendant carbonyl group to Ni 0 . This work advances our understanding of how common functional groups interact with Ni 0 catalysts and how these interactions affect workhorse catalytic reactions in academia and industry.